YIELD AND YIELD ATTRIBUTES OF RICE (Oryza sativa L.) AS INFLUENCED BY FOLIAR APPLICATION OF ZINC OXIDE NANOPARTICLES UNDER DIFFERENT CROP ESTABLISHMENT METHODS - T.N.K.V.K.PRASAD and S.NARENDER REDDY, BRIJBHOOSHAN, A.SRINIVAS, R.MAHENDRA KUMAR, T.RAM PRAKASH, K. AVIL KUMAR (The Journal of Research, PJTSAU, 2019)
A field experiment was conducted during rabi, 2015-16 and 2016-17 at ICAR-Indian Institute of Rice Research, Rajendranagar, Hyderabad to study the effect of nano zinc oxide foliar application in rice under different crop establishment methods. The experiment was laid out in split plot design with two establishment methods (direct seeding through dibbling under puddled condition and normal transplanting) in main plots and six nutrient management practices (Absolute control-no fertilizer, control-RDF NPK, RDF + soil application of ZnSO4.7H2O @ 25 kg ha-1, RDF + two foliar sprays of ZnSO4.7H2O at 0.5%, RDF + two foliar sprays of nano ZnO at 1000 ppm and RDF + two foliar sprays of nano ZnO at 1500 ppm) in sub-plots with four replications. The results revealed that number of panicles m-2 were significantly higher in direct seeded rice as compared to normal transplanting but other yield attributes like panicle length, panicle weight and filled grainsÂ  panicle-1 were significantly more in normal transplanted rice. Direct seeded rice recorded significantly higher grain yield (9.84, 8.85 and 9.45% during 2015, 2016 and pooled mean, respectively) as compared to normal transplanting. Among nutrient management practices, RDF + two foliar sprays of nano ZnO at 1000 ppm being at par with RDF + two foliar sprays of ZnSO4.7H2O at 0.5% and RDF + two foliar sprays of nano ZnO at 1500 ppm produced higher yield attributes i.e. number of panicles m-2, panicle length, panicle weight, grains panicle-1and test weight and grain and straw yield compared to other nutrient management practices.